Mapping the Distribution of Tourism Destinations in Les Village, Buleleng Regency - I Gusti Ayu Ema Manik Ayundari; Ima Anastasya; Stephanus Frisco Yunan Wicaksana; Made Dwipayana (Jurnal Ilmiah Ilmu Sosial, 2026)
The study aims to produce an accurate and up-to-date tourism destination map of Les Village that reflects the actual conditions in the field. The mapping process was carried out through field surveys, interviews with village officials and BUMDes tourism managers, as well as spatial analysis using a Geographic Information System (GIS). The data collected from observations and interviews include destination locations, access routes, and tourist accommodations. The results show that the previous map did not provide accurate information due to errors in its creation and did not display the distribution of accommodations in Les Village. The new tourism destination map identifies ten main destinations along with access routes and twelve accommodations, and can be independently updated by BUMDes. The study is expected to foster collaboration between the village government, academia, and local tourism stakeholders. With more comprehensive spatial information, the tourism destination map can serve as a foundation for sustainable and community-oriented tourism development planning.